2020
DOI: 10.13189/cea.2020.080508
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Mechanical and Durability Aspects of Concrete Modified with Steel Fibers (SFs)

Abstract: Concrete is weak in tension and strong in compression which results in brittle failure. This is obviously unacceptable for any construction materials. Thus, concrete requires some type of tensile reinforcement to balance its brittle behavior and improves its tensile strength. Adding of fibers is one of the most prevalent techniques to enhance the tensile behavior of concrete. Fiber slows cracking phenomena and increases energy absorption capacity of the structure. Majority researchers focus on mechanical perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 20 publications
3
71
0
Order By: Relevance
“…Although it has been reported that excess amount of coconut shell aggregates reduces strength due to poor bond between cement paste resulting in porous concrete. Fibers controls and constrain the development of cracks in concrete caused both in the plastic and hardened stage of concrete hence confirming a more durable concrete 30 , 31 , 33 . Furthermore, silica fume enhances density due to pozzolanic reaction i.e.…”
Section: Interpretation Of Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Although it has been reported that excess amount of coconut shell aggregates reduces strength due to poor bond between cement paste resulting in porous concrete. Fibers controls and constrain the development of cracks in concrete caused both in the plastic and hardened stage of concrete hence confirming a more durable concrete 30 , 31 , 33 . Furthermore, silica fume enhances density due to pozzolanic reaction i.e.…”
Section: Interpretation Of Resultsmentioning
confidence: 78%
“…Figure 5 presents the split tensile strength of different mixes while its standard deviation and coefficient of variation for 7 and 28 days is displayed in Table 8 . Adding glass fibers to concrete impressively enhances the concrete flexural and split tensile attributes during the hardened stage, for example, rigidity, flexural strength, toughness, and flexibility 30 . Past examinations have demonstrated that the consideration of fibers fundamentally enhances the split tensile strength of lightweight aggregate concrete 31 , 32 .…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…This is due to fact that steel fibers act as crack arresters and prevent the propagation of a crack in hardening concrete (Ahmad et al, 2020b). It has also been reported that, with the addition of superplasticizer, the workability of concrete improved, results in decreased voids in concrete (Borsoi et al, 2000;Ahmad et al, 2020b). Increasing voids' volume depicts lower bonding in concrete and can raise the ultrasonic pulse velocity of concrete (Ahmad et al, 2020b).…”
Section: Volume Of Voidsmentioning
confidence: 98%
“…The volume of voids increased from 14.62 to 18.45%. This is due to fact that steel fibers act as crack arresters and prevent the propagation of a crack in hardening concrete (Ahmad et al, 2020b). It has also been reported that, with the addition of superplasticizer, the workability of concrete improved, results in decreased voids in concrete (Borsoi et al, 2000;Ahmad et al, 2020b).…”
Section: Volume Of Voidsmentioning
confidence: 99%
See 1 more Smart Citation